2017
DOI: 10.1007/s12182-017-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification of Indian heavy crude oil using a novel surfactant for pipeline transportation

Abstract: The most economical way to overcome flow assurance problems associated with transportation of heavy crude oil through offshore pipelines is by emulsifying it with water in the presence of a suitable surfactant. In this research, a novel surfactant, tri-triethanolamine monosunflower ester, was synthesized in the laboratory by extracting fatty acids present in sunflower (Helianthus annuus) oil. Synthesized surfactant was used to prepare oil-in-water emulsions of a heavy crude oil from the western oil field of In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…Thus, it is a challenging process to decompose these chemicals in the refinery system, rendering them environmentally, unfriendly and costly. In this case, the surfactants used in this study could potentially act as cleaner and cheaper additives for crude oil with lower molecular weight and smaller molecules (Kumar and Mahto 2017;Gu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is a challenging process to decompose these chemicals in the refinery system, rendering them environmentally, unfriendly and costly. In this case, the surfactants used in this study could potentially act as cleaner and cheaper additives for crude oil with lower molecular weight and smaller molecules (Kumar and Mahto 2017;Gu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the emulsification process is significantly influenced by these parameters, as indicated in Table 2. Investigating the effect of surfactant concentration on the emulsification process, Kumar and Mahto [78] varied the surfactant concentration from 1 wt% to 3 wt% in intervals of 0.5 wt% and found that there was a drastic reduction in the emulsion viscosity of 96%. It was also observed that there was an increase in emulsion stability (from 80% to 100%) as the oil content increased (from 40% to 60%).…”
Section: Parameters Used For the Emulsification Formation Processmentioning
confidence: 99%
“…Essentially, within the reservoir or at the surface, the formation of emulsions is triggered by an energy input, which is traditionally supplied through shaking, stirring or some other kinds of intensive dynamic and/or static mixing forces. The process is usually aided by the presence of surface-active substances (such as synthetic chemical surfactant, natural hydrocarbon surfactant: asphaltene and resins and solid mineral particles) that contribute to stabilizing the particles of the dispersed phase (Clausse et al 2005;Martinez-Palou et al 2011Wong et al 2015;Wen et al 2016;Alade et al 2016a, b;Kumar and Mahto 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The popularly reported types of emulsions encountered in the petroleum industry include the binary-component waterin-oil (W/O) and oil-in-water (O/W) emulsions (Martinez-Palou et al 2011;Pal 2011;Balsamo et al 2014;Sefton and Sinton 2010;Mandal and Bera 2015;Alade et al 2016a;Zadymova et al 2017;Kumar and Mahto 2017). Several studies have been carried out on these types of emulsions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation